Sustainable Forage Production under Silvipastoral Systems in Semiarid Tropics - Bhatt, R.K.; Khan, T.A.; Pathak, P.S.; Mishra, A.K. (Indian Journal of Agroforestry, 2020)
The productivity and adaptation of Cenchrus ciliaris and Panicum maximum were studied under the canopies of fifteenyear- old trees of Acacia tortilis and Leucaena leucocephala and in open field in semi arid tropical environment. Full grown canopies of A. tortilis infiltered higher amount of photosynthetically active radiation (PAR, 50-55%) where as the canopies of L. leucocephala allowed only 30%. Under tree canopy temperature remains lower to the air temperature. The grass species accumulated higher amount of Chi a and Chi b under the shading environment of trees indicating their shade adaptation. Rate of photosynthesis (PN) transpiration (TR) and stomatal conductance (CS) reduced under tree canopies due to low availability of PAR. On average of the seven years. C. ciliaris and P maximum produced 4.20 t/ha and 6.84 Uha dry matter under tree canopies of A. tortilis and L. Leucocephala respectively. The total aboveground biomass productivity of the systems increased from 1.5 to 2.25 times when compared to only pasture land use system. The systems maintained higher soil moisture and organic carbon content for sustainable biomass production for longer period. Higher level of crude protein was estimated in the grasses grown under the tree canopies. DMY was closely associated with the available PAR under the tree canopies indicating that for sustainable production of these grasses for longer period about 40-60% PAR is required. Panicum maximum has shown high adaptability to shade and maintained carbohydrate and crude protein level, indicating potential for optimizing quality forage production to support the animal production.